The Effects of Physical Activity on Sleep among Adolescents and Adults: A Narrative Review - Sophie Desjardins; Manuel Tanguay-Labonté (Journal of Sleep And Sleep Disorder Research, 2018)
Objective: Examining the correlation between physical activity measures and sleep in normal adolescents and adult population. Methods: A systematic review was conducted on the effects of exercise, its intensity, its frequency and its timing and sleep outcome. Using the databases including MEDLINE, PsycINFO and SPORTDiscus, keywords used were “sleep”, “circadian rhythm”, “exercise”, and “physical activity”. Results: To improve the general quality of sleep amongst adolescents and adults, individuals should engage in physical activity at any time of day. It also appears very advantageous to engage in long-term physical activity to maintain the positive effects on sleep. Nonetheless, it seems that sedentary individuals can also benefit from occasional physical activity to improve the quality of their subsequent sleep period. Conclusion: A virtuous relationship between physical activity and sleep may exist in normal adolescents and adults. People should seek to benefit from this link to improve both the quality of their sleep and of their daily functioning. However, larger scale studies, controlling for variables might help to better delineated this relationship.
Keywords: sleep